Anatomical data on the intracranial venous drainage of the tufted capuchin, Cebus apella linnaeus, 1758 - Madeira, Miguel C.; Watanabe, Ii‐Sei (Wiley, 1975)
The venous channels responsible for the intracranial drainage were dissected in a series of 25 male and female adult tufted or brown capuchin monkeys (Cebus apella). It was found that Cebus have a venous arrangements fundamentally the same as in man, differing only in that: 1. the monkey has no inferior sagittal sinus, sphenoparietal sinus, and emissary parietal and condylar veins; 2. the occipital sinus is not in connection with other sinuses; 3. there are a sphenopetrosal sinus, a petrosquamous sinus, and an unpaired inferior cerebellar vein; 4. besides the internal jugular vein, there is additional intracranial drainage through the petrosquamous sinus and the postglenoid vein; 5. the superficial middle cerebral vein opens into the petrosquamous sinus; 6. the lingual and facial veins are not tributaries of the internal jugular vein; 7. there is a bilateral uniform division of the superior sagittal sinus at the confluence of the sinuses to drain equally into both transverse sinuses; 8. the vascular pattern appears to be quite stable; anatomical variations appear to be few and unimportant. Copyright © 1975 Wiley‐Liss, Inc.